Existence of Nonoscillatory Solutions for Mixed Neutral Fractional Differential Equation - Muthulakshmi, Velu; Pavithra, Subramani (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we establish some sufficient conditions for the existence of nonoscillatory solution for a class of mixed neutral fractional differential equations with Liouville fractional derivative of order α ≥ 0 on the halfaxis. Our results generalize some of the existing results in the literature. Some examples are given to illustrate our results.